Factors Affecting Motivation for Career Selection of Public Accountants - Budiandru, Budiandru (AKRUAL: JURNAL AKUNTANSI, 2021)
The purpose of this study was to determine the influence of intrinsic value, work environment, and job market considerations on the motivation to choose a career as a public accountant either partially or simultaneously. This research method uses multiple linear regression analysis with a sample of 210 students of the faculty of economics and Business, University of Muhammadiyah Prof. Dr. Hamka. The research results based on the t-test show that the intrinsic value of work affects the motivation for choosing a career to become a public accountant, while the work environment and job market considerations do not affect the motivation for choosing a career to become a public accountant. Simultaneously, the intrinsic value of work, work environment, and labor market considerations affect the motivation to choose a career to become a public accountant. Public accounting firms need to consider workspace and freedom for auditors to complete existing work, providing intellectual challenges with a dynamic work atmosphere.